Utilizing Compact 4G LTE Mobile Stations to Enhance Network Coverage in Rural Low-Signal Areas - Sirmayanti Sirmayanti; Muh. Ilham Ihsary; Ichsan Mahjud (Jurnal IPTEK, 2025)
A bad spot is an area where signal quality fails to meet Key Performance Indicator (KPI) standards, due to factors such as limited channel capacity, BTS malfunctions, long distances from the BTS, or topographical interference. This study investigates a 4G LTE bad spot case in the rural area of Romanglasa Subdistrict where RSRP levels range from -100 dBm to -120 dBm. Although several e-nodeBs are present around the area, physical obstructions like trees and buildings continue to degrade signal quality. The objective of this study is to effectively implement a Compact Mobile Station (COMBAT), analyze the installation process, and evaluate the network's performance after deployment. The methods used include drive testing, BTS site surveys, simulations, and network design. The installation was carried out in collaboration with Telkomsel using Combat-571 as the cell ID. Following deployment, network quality measurements and post-drive testing were conducted. The results showed significant improvements: download throughput reached 47.6 Mbps, upload 28.4 Mbps, jitter decreased to 7 ms, packet loss dropped to 0%, and latency was reduced to 21 ms. Post-installation RSRP also improved to between -80 dBm and -100 dBm, categorized as good to fair according to KPI standards.